Collective Bargaining and Innovation in Germany: Cooperative Industrial Relations? - John T. Addison; Paulino Teixeira; Katalin Evers; Lutz Bellmann (Institute for the Study of Labor (IZA), 2013)
The effect of collective bargaining on innovation has long been in dispute. At the level of theory, the hold-up problem has been used to justify positive as well as negative effects of unionism. At the empirical level, although some would consider the North American evidence as cut and dried, this is not the case for other countries. In Europe there is some suggestion that certain industrial relations systems, either alone or in combination with the regulatory framework in which they are embedded, may tip the balance in favor of a beneficial union effect. In the present paper, we assemble nationally representative data for Germany for many observers the exemplar of a cooperative industrial relations regime to investigate the impact of collective bargaining on (several measures of) process innovation and product innovation. Our cross section and longitudinal analysis fails to indicate that unionism retards innovation. Indeed, in conjunction with workplace representation, collective bargaining at sectoral level might even be pro innovative.
Keywords: J51; J53; O31; 330; Germany; collective bargaining; innovation